Applications of halloysite nanotubes in food packaging for improving film performance and food preservation. (June 2021) - Li, Qingqing; Ren, Tian; Perkins, Phil; Hu, Xiaofeng; Wang, Xiaolong
Abstract: Food packaging, particularly active packaging, plays an important role in maintaining food quality and safety. Incorporating antimicrobial agents into films usually enhances the antimicrobial activity, but easily provokes a burst release of antimicrobials and degrades film performance. Recent studies found that addition of reinforcement agents effectively improved mechanical strength and barrier properties of packaging films. Halloysite nanotubes (HNTs) are natural clays with a unique tubular structure, possessing large surface areas and negatively charged exteriors. These properties do not only prepare HNTs as a satisfactory reinforcement agent, but also enable active agents to be loaded into the lumen or attached to the exteriors of HNTs, achieving a sustained controlled release of antimicrobials. HNTs have shown great application potential in the food industry, but currently there are no systematic reviews in this field. This review is focused on HNTs' roles as nano-filler and nano-carrier when incorporated into food packaging systems, improving food preservation without sacrificing film performance. Effects of incorporation techniques and polymeric matrixes on film behavior were systemically reviewed, with a profound explanation on the mechanisms of carrying food preservatives. In addition, antimicrobial activities and release kinetics of HNTs based active agents were discussed in detail. Current problems and directions for the future applications of HNTs in food packaging system were analyzed in the end. In conclusion, proper use of HNTs in food packaging system is a promising way to achieving controlled release of antimicrobials, enhancing the quality and safety of fresh food during storage and transportation. Highlights: Direct incorporation of antimicrobials into films easily provokes a burst release. HNTs in food packaging enhanced the quality and safety of fresh food. Mechanisms of improving film behavior and carrying preservatives were discussed. Antimicrobial activities and release kinetics of HNTs based active agents were reviewed. Current problems and future directions for HNTs in food packaging were analyzed.